2021
DOI: 10.1007/s11109-021-09697-8
|View full text |Cite
|
Sign up to set email alerts
|

Does Radical-Right Success Make the Political Debate More Negative? Evidence from Emotional Rhetoric in German State Parliaments

Abstract: Political rhetoric has important effects on the quality of democracy, but we know very little about what causes variation in the tone of the political debate. We investigate how radical-right success affects the way the remaining politicians discuss political issues. Using an original dictionary, we measure different positive and negative emotions in a newly collected dataset of speeches in German state parliaments. Taking advantage of variation in the timing of elections when radical-right politicians enter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 60 publications
2
10
0
1
Order By: Relevance
“…5 Der aktuelle Forschungsbedarf für die Landesparlamente resultiert jedoch nicht nur aus einer akademischen Randlage (für Ausnahmen mit komparativer Ausrichtung vgl. Appeldorn und Fortunato 2021 ; Atzpodien 2020 ; Valentim und Widmann 2021 ), die für sich genommen eine wissenschaftliche Untersuchung nicht hinreichend rechtfertigen kann, sondern zweitens aus deren Bedeutung als regionale Hochburgen der föderalen Demokratie in Deutschland: Die Landesparlamente sind die einzigen direkt durch Wahlen legitimierten Institutionen der politischen Systeme der Länder (vgl. Mielke und Reutter 2012 ; Sturm 2020 ).…”
Section: Introductionunclassified
“…5 Der aktuelle Forschungsbedarf für die Landesparlamente resultiert jedoch nicht nur aus einer akademischen Randlage (für Ausnahmen mit komparativer Ausrichtung vgl. Appeldorn und Fortunato 2021 ; Atzpodien 2020 ; Valentim und Widmann 2021 ), die für sich genommen eine wissenschaftliche Untersuchung nicht hinreichend rechtfertigen kann, sondern zweitens aus deren Bedeutung als regionale Hochburgen der föderalen Demokratie in Deutschland: Die Landesparlamente sind die einzigen direkt durch Wahlen legitimierten Institutionen der politischen Systeme der Länder (vgl. Mielke und Reutter 2012 ; Sturm 2020 ).…”
Section: Introductionunclassified
“…Existing studies investigating the emotional framing of messages in political communication suggest that political parties use emotive content in a strategic manner, depending on their policy positions (Kosmidis et al, 2019 ), the economic situation (Crabtree et al, 2020 ), the success of political competitors (Valentim & Widmann, 2021 ), or the temporal direction of statements (Müller, 2022 ). Moreover, research has found that emotional appeals are dependent on the incumbency status and the position in the political space.…”
Section: Emotional Rhetoric In Political Communicationmentioning
confidence: 99%
“…A growing strand of literature researches the affective side of political communication. These studies argue that politicians use emotional rhetoric strategically (Crabtree et al, 2020 ; Kosmidis et al, 2019 ; Müller, 2022 ; Valentim & Widmann, 2021 ). Furthermore, the general pattern found is that incumbents make more use of positive emotional appeals, while opposition parties (and especially challenger parties on the fringes of the political spectrum) make greater use of negative emotional language.…”
mentioning
confidence: 99%
“…The within-county research design further holds constant any differences in the party supply that may relate to the organization of the populist right 'on the ground,' i.e., its organization in county-level party branches. As counties are administrative units below the level of the sixteen different German states, the design also accounts for differences in the party system supply between regions prompted by the representation of the populist right in some state parliaments (Valentim and Widmann, 2021). I further include other municipal-level characteristics that may systematically relate to both the success of the populist right AfD and a latent demand for populist right policies prior to the party's existence.…”
Section: Data and Research Designmentioning
confidence: 99%